2004
DOI: 10.1209/epl/i2004-10189-2
|View full text |Cite
|
Sign up to set email alerts
|

Spin splitting in open quantum dots

Abstract: We demonstrate that the magnetoconductance of small lateral quantum dots in the stronglycoupled regime (i.e. when the leads can support one or more propagating modes) shows a pronounced splitting of the conductance peaks and dips which persists over a wide range of magnetic fields (from zero field to the edge-state regime) and is virtually independent of the magnetic field strength. Our numerical analysis of the conductance based on the Hubbard Hamiltonian demonstrates that this is essentially a many-body/spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…[7] had relatively large electron density (n s ∼ 2 × 10 15 m −2 ), whereas the dots in Ref. [9] had low electron density, (n s < 7×10 14 m −2 ), such that the observed features [7,9] are consistent with our findings that spin polarization diminishes as the electron density in the dot increases.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…[7] had relatively large electron density (n s ∼ 2 × 10 15 m −2 ), whereas the dots in Ref. [9] had low electron density, (n s < 7×10 14 m −2 ), such that the observed features [7,9] are consistent with our findings that spin polarization diminishes as the electron density in the dot increases.…”
supporting
confidence: 88%
“…At the same time, the results of Ref. [9] suggested that the spin degeneracy in open dots is lifted. Our findings reported above seem to reconcile these apparently different experimental observations.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The phenomena has been suggested to occur in various systems including quantum point contacts 1 ͑QPCs͒, two-dimensional electron gas ͑2DEG͒, 2,3 quantum wire, 4 and open quantum dots. 5 Theoretical modeling with Hartree-Fock, 6 the density functional theory, 5,[7][8][9] and Monte Carlo simulations 10 has reproduced low density spin polarization in a number of systems. The mechanism driving the polarization is the exchange energy dominating over the kinetic energy at low densities, making the spin-polarized state the energetically most favorable.…”
Section: Introductionmentioning
confidence: 99%